Viscosity and Surface Tension of Benzene at Saturation Conditions from Surface Light Scattering - Kerscher, Manuel; Fröba, Andreas Paul; Koller, Thomas Manfred (International Journal of Thermophysics, 2021)
In the present study, the liquid viscosity and surface tension of benzene was determined at saturation conditions from surface light scattering (SLS) experiments between (283 and 393) K. Based on the application of the hydrodynamic theory for surface fluctuations at the vapor-liquid phase boundary which was successfully validated by the measurements, a simultaneous determination of liquid viscosity and surface tension with average relative expanded uncertainties (k = 2) of (1.0 and 0.8)% was achieved. Agreement between the measurement data and reference values available in the literature was found for the viscosity and in general also for the surface tension, where benzene constitutes a recommended reference material of relatively moderate surface tension values. All these findings demonstrate for a repeated time that SLS is a suitable method for the investigation of fluids including reference fluids such as benzene, which enables a sound representation of its surface tension, presumably as a result of a rather random molecular orientation at the surface. Overall, the experimental results from this work could contribute to an improved data situation for benzene, in particular with respect to providing viscosities and surface tensions at true saturation conditions.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Benzene; Surface light scattering; Surface tension; Viscosity